Stress response of NAD+-dependent formate dehydrogenase in Gossypium hirsutum L. grown under copper toxicity - Kurt-Gur, Guenseli; Demirci, Hasan; Sunulu, Akin; Ordu, Emel (SPRINGER HEIDELBERG, 2018)
Cotton (Gossypium hirsutum L.), which is not directly involved in the food chain, appears to be a suitable candidate to remove heavy metals from the food chain and to be a commercial plant which could be planted in contaminated soils. The key point of this approach is selection of the right genotype, which has heavy metal resistance or hyperaccumulation properties. Therefore, in the present study, two G. hirsutum genotypes, Eran-92 and N-84S, were grown under copper stress and investigated to obtain further insights about the heavy metal tolerance mechanisms of plants by focusing on the expression of NAD(+)-dependent formate dehydrogenase (FDH). In accordance with the results, which were obtained from RT-PCR analysis and activity measurements, in the Eran-92 root tissue, FDH activity increased significantly with increasing metal concentrations and a 6.35-fold higher FDH activity was observed in the presence of 100-mu M Cu. As opposed to Eran-92, the maximum FDH activity in the roots of N-84S, which were untreated with copper as the control plants, was measured as 0.0141-U mg(-1) g(-1) FW, and the activity decreased significantly with the increasing metal concentrations. The metallothionein (GhMT3a) transcript level of the plants grown in a medium containing different Cu concentrations showed nearly the same pattern as that of the FDH gene transcription. It was observed that while the tolerance of N-84S in the lower Cu concentration reduces remarkably, Eran-92 continues to struggle up to 100-mu M Cu. The results of the SOD analysis also confirm this activity of Eran-92 against the Cu stress.
Keywords: Upland cotton; Gossypium hirsutum; Formate dehydrogenase; Metallothionein; Copper stress; H2O2 content; Lipid peroxidation level; SOD activity; OXIDATIVE STRESS; CADMIUM STRESS; COTTON; TOLERANCE; METALLOTHIONEINS; CULTIVARS; EFFICIENT; SEEDLINGS; ENZYMES; BINDING; Environmental Sciences & Ecology